Pengembangan Pendekatan Creative Problem Solving - Pratiwi Pratiwi; Haslinda Haslinda; Khalik Khalik; Tri Wijaya; M. Yasdar; Husni Husni; Elihami Elihami; Adi Adi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
Students' creative thinking skills are competencies that must be developed to face the future in the era of the industrial revolution 4.0. The research was carried out on the third semester students of Nonformal Education at the University of MUhammadiyah Enrekang. The purpose of student and lecturer activities during the lecture process with a scientific approach is to describe students' creative thinking skills through a scientific approach. This study uses a critical review through field research. The instruments used in this study were student and lecturer activity observation sheets during learning and student creative thinking test sheets. The results showed that there was an increase in students' creative thinking skills with a percentage of 70% in the initial stage to 76% in the second stage, lecturer activity also increased from 79% in the first stage to 81% in the second stage. Meanwhile, student activity increased from 75% in the first stage to 78 in the second stage. Based on the results of this study, lecturers are advised to apply a scientific approach to develop other competencies needed in the era of society 5.0.